An efficient method for isolating mating‐competent cells from bottom‐fermenting yeast using mating pheromone‐supersensitive mutants. Issue 1 (16th January 2018) - Ota, Taku; Kanai, Keiko; Nishimura, Hisami; Yoshida, Satoshi; Yoshimoto, Hiroyuki; Kobayashi, Osamu
Abstract: Crossbreeding is an effective approach to construct novel yeast strains with preferred characteristics; however, it is difficult to crossbreed strains of brewer's yeast, especially the bottom‐fermenting yeast Saccharomyces pastorianus, because of the relative inefficiency of the available methods to obtain mating‐competent cells (MCCs). Here, we describe a productive method for the isolation of MCCs without artificial genetic modification. We focused on the characteristics of two mating pheromone‐supersensitive mutants, Δbar1 and Δsst2, that show a growth defect in the presence of the mating pheromone. When MCCs secreting α ‐factor and a‐factor were spotted on to a lawn of MATa Δbar1 and MATα Δsst2, a halo was observed around the respective MCCs. This plate assay was successful in identifying MCCs from bottom‐fermenting yeast strains. Furthermore, by selecting for cells that caused the growth defect in pheromone‐supersensitive cells on cultures plates, 40 α / α ‐type and six a/a‐type meiotic segregants of bottom‐fermenting yeast strains were successfully isolated and crossed with tester strains to verify their mating type. This method of isolation is expected to be applicable to other industrial yeast strains, including wine, sake and distiller's yeasts, and will enable MCCs without genetic modifications to be obtained. As a result, it will be a useful tool for more convenient and efficient crossbreeding of industrial yeast strains that can be applied to practical brewing. Copyright © 2017 John Wiley & Sons, Ltd.